Clinical outcome of stereotactic body radiotherapy of 54 Gy in nine fractions for patients with localized lung tumor using a custom-made immobilization system - Aoki, Masahiko; Abe, Yoshinao; Kondo, Hidehiro; Hatayama, Yoshiomi; Kawaguchi, Hideo; Fujimori, Akira; Suzaki, Katsumasa; Seino, Morio; Morita, Takeshi; Souma, Makoto; Tsushima, Takao; Takanashi, Shingo (Japanese journal of radiology, 2007)
The aim of this study was to investigate the clinical outcome of stereotactic body radiotherapy (SBRT) of 54 Gy in nine fractions for patients with localized lung tumor using a custom-made immobilization system. The subjects were 19 patients who had localized lung tumor (11 primaries, 8 metastases) between May 2003 and October 2005. Treatment was conducted on 19 lung tumors by fixed multiple noncoplanar conformal beams with a standard linear accelerator. The isocentric dose was 54 Gy in nine fractions. The median overall treatment time was 15 days (range 11-22 days). All patients were immobilized by a thermo-shell and a custom-made headrest during the treatment. The crude local tumor control rate was 95% during the follow-up of 9.4-39.5 (median 17.7) months. In-field recurrence was noted in only one patient at the last follow-up. The Kaplan-Meier overall survival rate at 2 years was 89.5%. Grade 1 radiation pneumonia and grade 1 radiation fibrosis were observed in 12 of the 19 patients. Treatment-related severe early and late complications were not observed in this series. The stereotactic body radiotherapy of 54 Gy in nine fractions achieved acceptable tumor control without any severe complications. The results suggest that SBRT can be one of the alternatives for patients with localized lung tumors.